Теоретичне обґрунтування основних параметрів колісних сільськогосподарських тракторів - Ребров, Олексій Юрійович (Харківський національний технічний університет сільського господарства ім. Петра Василенка, 2017)
В статті запропоновано теоретичне обґрунтування нового підходу до визначення основних параметрів колісних сільськогосподарських тракторів тягової концепції. Наведений підхід відрізняється від класичних уявлень і базується на врахуванні вирішального впливу тракторних шин на сумісний вибір маси трактора, номінальної сили тяги на гаку, потужності двигуна, розподіл маси по ведучим мостам. Критерієм якості вибору виступають техніко-економічні показники трактора і машино-тракторного агрегату.

This article presents the theoretical justification of a new approach to defining basic parameters of wheeled farm tractors of traction concept. A new approach differences from the classical concepts is based on decisive influence of tires on choice of tractor mass, drawbar performance, engine power, weight distribution on the driving axles. A technical and economic indicator of tractors and machinery tractor unit is selected as the criterion of choice quality. It is shown, that the choice of engine power and speed mode tillage is not straightforward and can be resolved by criteria of maximum productivity or minimum fuel consumption. The approach to theoretical justification of wheeled agricultural tractors parameters can be further refined on a base of soil-climatic conditions of Ukraine.
Theoretical justification of the basic parameters of wheeled farm tractors
Keywords: колісний трактор; тракторна шина; параметри трактора; wheeled tractor; tractor tire; tractor parameters